Novel pyran-based anti-inflammatory agents: design, synthesis, and mechanistic studies in LPS-stimulated macrophages - Mei Tong He; Sung Jin Kim; Viet Duc Le; Su Ji Min; Heesu Lee; Jae Wook Lee; Myoung-Sook Shin (Applied Biological Chemistry)
Abstract This study investigated the anti-inflammatory effects of pyran derivatives, focusing on compound 19, in LPS-stimulated RAW264.7 macrophages. We screened 19 pyran derivatives for cytotoxicity and nitric oxide (NO) inhibition, and identified compound 19 as the most promising compound owing to its efficacy. Western blot analysis revealed that compound 19 significantly inhibited the expression of key inflammatory mediators such as inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 in LPS-stimulated macrophages in a dose-dependent manner. Furthermore, compound 19 inhibited the phosphorylation of Akt at 12.5 μM, and suppressed JNK and ERK MAPK phosphorylation at both concentrations (12.5 and 6.25 μM), while p38 phosphorylation was not inhibited. These findings suggest that compound 19 exerts its anti-inflammatory action by modulating multiple signaling pathways involved in inflammatory responses. Our results demonstrate that compound 19 is a promising candidate for the development of novel anti-inflammatory agents.